Achieving sustainability in Nigerian higher education institutions: responsive role of the leaders - Ayodele, Lasisi Abass; Mohd Ali, Hairuddin (AIMS Research Journal, 2015)
It is undoubted that we are now living in turbulent era where teaching-learning and administration of higher education institutions (HEI) are facing many difficulties. This is because everything is growing at a fast pace and the future is uncertain. Revisiting the mission of higher education and achieving sustainability in HEI are lacking attention. These have been the top topic discussion addressing in various conferences and literatures. If leaders make sustainability a communicable concept and be their responsive roles in HEI, a priority towards sustaining the future of HEI would be achieved. This paper focuses on leadership roles and explores the literatures pertaining to sustainability in HEI. As a new area in the literatures, this study brings connections between leadership roles and sustainability process as a responsive way in facing the various challenges confronting HEIs. The study discusses the possibility towards the sustainability in HEI allied with a relevant model for future achievement. Keywords: Leadership, Sustainability, Nigerian Higher Education